Rapid clinical progression to AIDS and death in a persistently seronegative HIV-1 infected heterosexual young man - Bartolo, Ines (2015)
Seronegative HIV-1 infection has important implications for diagnosis and prevention. We describe a case of HIV-1 infection without sero-conversion and fast progression to AIDS and death. Genetic and phylogenetic analysis indicated that the patient was in. - Comissao Nacional de Luta Contra a SIDA, Portugal [CRIA-CR3751]. - The clinical and laboratorial contributions of Manuela Mana and Sandra Bento for the early identification and study of these patients are gratefully acknowledged. Author's contributions: N.T, R.C., and VB. designed the research. N.T, R.C., V.B., I.B. and